Mitigation of thermally-induced performance limitations in coherently-combined multicore fiber amplifiers - Steinkopff, Albrecht; Aleshire, Christopher; Klenke, Arno; Jauregui, Cesar; Limpert, Jens (Optics Express, 2022)
Multicore fiber (MCF) amplifiers have gained increasing interest over the past years and shown their huge potential in first experiments. However, high thermal loads can be expected when operating such an amplifier at its limit. Especially in short MCF amplifiers that are pumped in counter-propagation, this leads to non-uniform mode-shrinking in the cores and, consequently, to a degradation of the system performance. In this work we show different ways to counteract the performance limitations induced by thermal effects in coherently-combined, multicore fiber amplifiers. First, we will show that pumping MCFs in co-propagation will significantly improve the combinable average power since the thermal load at the fiber end is reduced. However, this approach might not be favorable for high energy extraction. Therefore, we will introduce a new MCF design pumped in counter-propagation that leads to a reduction of the thermal load at the fiber end, which will allow for both high combined output power and pulse energy.
CRIS-Team Scopus Importer:2023-04-20